REACTIVE THROMBOCYTOSIS FOLLOWING ACUTE INFECTION AND PANCYTOPENIA: Reactive Thrombocytosis - Abbas, Syed Waqar; Hussain, Tassawar; Zareen, Syeda Fatimah (Pakistan Armed Forces Medical Journal, 2008)
.